A tool for semantic data interoperability - Santana, Allan Patrick F.; C. Junior, Maximilian Harrisson; Lopes, Bruno (Anais do Workshop Brasileiro de Lógica (WBL); 2023: Anais do IV Workshop Brasileiro de LógicaDO - 10.5753/wbl.2023.230027, 2023)
Over the years, the amount of information available to the public by digital means is growing more and more, however, this growth is done in a fragmented way by several companies. Integrating these data may lead to inconsistencies, and system errors. This integration may be difficult and expensive for companies. Data interoperability is done when data with distinct formats or from multiple sources are processed to generate unified data. This work presents a tool to make automatic alignment of data from multiple sources, integrating with the SUMO ontology so that inferences can be made with the tool